Hemodynamic forces tune the arrest, adhesion, and extravasation of circulating tumor cells - Follain, Gautier; Osmani, Naël; Azevedo, Ana Sofia; Allio, Guillaume; Mercier, Luc; Karreman, Matthia A.; Solecki, Gergely; Garcia Leòn, Marìa Jesùs; Lefebvre, Olivier; Fekonja, Nina; Hille, Claudia; Chabannes, Vincent; et al. (Developmental cell, 2018)
Metastatic seeding is driven by cell-intrinsic and environmental cues, yet the contribution of biomechanics is poorly known. We aim to elucidate the impact of blood flow on the arrest and the extravasation of circulating tumor cells (CTCs) in vivo. Using the zebrafish embryo, we show that arrest of CTCs occurs in vessels with favorable flow profiles where flow forces control the adhesion efficacy of CTCs to the endothelium. We biophysically identified the threshold values of flow and adhesion forces allowing successful arrest of CTCs. In addition, flow forces fine-tune tumor cell extravasation by impairing the remodeling properties of the endothelium. Importantly, we also observe endothelial remodeling at arrest sites of CTCs in mouse brain capillaries. Finally, we observed that human supratentorial brain metastases preferably develop in areas with low perfusion. These results demonstrate that hemodynamic profiles at metastatic sites regulate key steps of extravasation preceding metastatic outgrowth.